The Analysis of Child Bullying Behaviour of Game Mobile Learning Users, in The Early Childhood Education Management Perspective - Aisyah, Eny Nur; Harun, Harun; Rohman, Arif; Hardika, Hardika (International Journal of Interactive Mobile Technologies (iJIM), 2021)
This study aims to analyze the behavior of verbal bullying, social bullying, and physical bullying in early childhood using game mobile learning. The research approach used is qualitative phenomenology. The informants of this study were 24 parents, 3 teachers, and 30 children aged 4-6 years in Early Childhood Education Institutions in Indonesia. Data were collected through in-depth interviews, observation, and documentation study. Based on the results of data analysis, it is known the behavior of verbal bullying, social bullying, and physical bullying there are differences in the intensity and frequency of bullying behavior of children aged 4-6 years while playing game mobile learning at home and in social settings. Unconsciously, bullying behavior is formed and developed from an early age through game mobile learning used by children. Children do not understand the meaning of bullying behavior which is shown through attitudes, words, and behavior when playing game mobile learning. So, the closest adults to the child are needed (1) to manage learning activities using game mobile learning, (2) provide intensive assistance for children when playing game mobile learning, (3) provide good advice and admonitions when bullying behavior is presented by the child, (4) agree on clear rules, and (5) firmly with children when playing game mobile learning